Instrumental characteristics and acid blue 193 dye sorption properties of novel lupine seed powder - A. Hashem; Chukwunonso O. Aniagor; E.S. Abdel-Halim; A. Amr; S. Farag; A.A. Aly (Cleaner Chemical Engineering, 2022)
Due to their high seed protein content (36 to 42% of the dry weight), lupine seed serve as a valuable nutritional source for low-income populations. Unfortunately, the high protein content which makes them highly desirable also turns them into food allergens, thus justifying its alternative application as an adsorbent. Therefore, this study explored the potential of lupine seed powder (L-SP) as a novel, efficient and low-cost adsorbent for the uptake of acid blue 193 dye. The adsorption process was evaluated via batch mode, under the influence of several process variables (such as initial dye concentration, 10–100 mg/L; temperature, 30 – 70 °C; adsorbent dosage, 0.2 – 3.0 g/L; solution pH, pH 2.0 – 10.0 and contact time, 1 – 180 min). The structural and morphological characteristics of the l-SP adsorbent, as well as its elemental composition, was elucidated from the Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy dispersion X-ray (EDX) analyses. A maximum adsorption capacity of 144.56 mg/g was obtained at 25 °C. The thermodynamic investigation suggests a prevailing endothermic process, thus adsorption is enhanced at an increased degree of freedom between the adsorbent and adsorbate solution interface.